The Principle of Sustainable Development in Good Mining Practice: A Legal Review of Equitable and Beneficial Nickel Mining Governance in Indonesia - Jaqueline Margareth Sahetapy; A Afdhal (Journal Customary Law, 2026)
In the dynamics of the global political economy, nickel is no longer just a mining commodity but a strategic resource that influences industrialization, energy technology, and the stability of the global supply chain. Indonesia, as the world's largest nickel producer, plays a crucial role in meeting the growing global demand for nickel. Projections from the International Nickel Study Group (INSG) indicate that global nickel consumption is expected to reach 3.824 million tons in 2026, up from 3.601 million tons in 2025, driven primarily by the stainless steel and energy technology industries. Normatively, the management of mineral resources is regulated in Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia, which affirms that natural resources are controlled by the state and utilized to the greatest extent for the prosperity of the people. This provision is reinforced by Law Number 3 of 2020 concerning Mineral and Coal Mining, which mandates sustainable mining management through the implementation of Good Mining Practice principles. However, in fact, nickel mining expansion still gives rise to various problems, including environmental degradation, ecosystem damage, and inequality in the use of natural resources, which ultimately leads to injustice for communities around mining areas. This study aims to analyze the application of Sustainable Development principles within the Good Mining Practice concept to nickel mining governance in Indonesia to achieve equitable and beneficial management. This research employs a normative juridical method with a legislative approach and a conceptual approach through an analysis of mining regulations, including Regulation of the Minister of Energy and Mineral Resources Number 26 of 2018 concerning the Implementation of Good Mining Principles and Supervision of Mineral and Coal Mining. The research results show that the principles of sustainable development have been normatively integrated into the national mining legal framework through the implementation of Good Mining Practices, which encompass occupational safety, environmental protection, post-mining reclamation, and corporate social responsibility. However, its implementation still faces challenges in balancing economic interests, environmental protection, and community welfare. Therefore, strengthening legal governance in the mining sector based on sustainable development principles is essential to ensure that nickel resource management is sustainable, equitable, and beneficial for national development.